TEOLOGI DALAM KIDUNG RUMEKSA ING WENGI - Anita Ulyati Azizah; Arif Hidayat (Mediakita, 2021)
This study aims to explore the meaning of Kidung Rumeksa Ing Wengi which played a role in the spread of Islam in Java. This research was conducted textually with structural analysis, namely the intrinsic and extrinsic analysis of the text. In this study, it is proven that the Song of Rumeksa Ing Wengi created by Sunan Kalijaga aims as a means of preaching Islam by combining Islamic teachings and the traditions of Javanese society at that time so that Javanese people easily accept and understand Islamic teachings. Until now, this song is still often hummed by the Javanese community which is one of the heritages that must be preserved. This research also proves that there are intrinsic and extrinsic elements in the text of Kidung Rumeksa Ing Wengi, intrinsic elements which contain the language used by Sunan Kalijaga to preach, which is very unique, mystical, the style of language is full of figure of speech, which is able to influence the nature of thought and imagination. the readers. While the extrinsic elements are theological values such as how to interpret God, humans, and the relationship between God and humans, besides that there are concepts and values that can be taken such as ethics when praying, ethics with wasilah, and the concept of riyadhoh or selfcontrol.